Pendekatan Terintegrasi Corporate Social Responsibility Perbankan Syariah dalam Pengentasan Kemiskinan di Jawa Timur - Ahmad Hudaifah (Al Tijarah, 2016)
As one of Indonesian province playing barometer for the development of Islamic economic and Muslim aspiration, the Islamic banking presence in East Java is expected to have broader social role in poverty alleviation process. Through synergy process with stakeholders, a relatively new approach to support government program needs to be analyzed its feasibility. Study about integrated approaches on corporate social responsibility is necessary to undertake in order to comprehend the possible space and opportunity in enhancing East Java’s poverty reduction program. Methodology of study employing qualitative analysis with library research is done to answer potency and feasibility of CSR program in East Java. The result of study has concluded that although CRS concept is not relatively new in Islamic Economics, this strategy has been selected to sound inclusive and acceptable terminology for stakeholders involved. Integrated-CSR strategy approaches led by Islamic banking require an institution (SPV-special purpose vehicles) that can manage CSR fund productively and sustainably. This program must be supported by the availability of zakat (alms) fund as the pillars to provide basic needs for the poor. After the poor people (dhuafa) are able to fulfill their basic needs, the East Java’s micro-enterprises programs are effectively introduced in empowering them.